Hybrid iterative equalizer for massive MIMO millimeter wave CE-OFDM systems - Enes, Ricardo (2020)
The next generation, the fifth-generation (5G), is expected to deliver unprecedented data transmission speeds, lower latency, and the capacity to connect everything and everyone. However, accomplishing these features faces some challenges, such as the limited availability of bandwidth in the conventional sub-6GHz band. This constraint has induced telecommunications operators and the research community to develop solutions that combine both the use of the millimeter-wave band (mmWave) and massive MIMO systems. These technologies present a symbiotic relationship that can provide the high transmission rates envisioned for future 5G systems and circumvent the scarcity of bandwidth. However, the large number of antennas envisioned for future wireless systems makes it impossible to use a fully digital architecture due to the hardware constraints. Additionally, it is also not resolvable to have a system that works only in the analog domain by employing full analog beamforming since the performance is poor. To overcome these limitations, hybrid analog-digital architectures, where some signal processing is done at the digital level and some left to the analog domain, have been proposed in the literature. In such architectures the number of radiofrequency chains is lower than the number of antennas, thus reducing the hardware complexity. This work addresses the implementation of an iterative hybrid two-step space-frequency receiver structure for multiuser uplink millimeter wave (mmWave) massive MIMO based systems. We adopt constant envelope OFDM (CE-OFDM), a promising modulation technique for future mmWave wireless communications, that enables low-cost power amplification and high efficiency, using highly nonlinear amplifiers. The user terminals (UTs) are equipped with a single radiofrequency (RF) chain. In the transmission we consider two different analog precoders. The first one consists in a set of random analog phase shifters, while the second is based on the average angles of departure of the channel. On the receiver side, we adopted a hybrid analog-digital nonlinear multiuser equalizer, based on the iterative block decision feedback equalization (IB-DFE) principle, designed to remove inter-user and inter-carrier interferences efficiently. The results show that the proposed equalizer converges requiring only a few numbers of iterations. Furthermore, the achievable performance is close to the one obtained for the full digital counterpart.